Socio-Economic Status and Language Development in Hearing Loss: A Critical Appraisal - Binos, Paris; Papastefanou, Theodora; Psillas, George K. (My University, 2023)
The impact of language input on children’s speech, language, and brain development was borne out of Hart and Risley’s famous “30-million-word gap”. A perspective bolstered by many studies in the last decade relates higher socio-economic status (SES) to better qualitative and quantitative differences in children’s speech. The logic chains found in these studies suggest that literacy development depends on language and brain development. Thus, brain building develops based on environmental experience and language input depends on the brain’s perception of the auditory information. This essay uses the latest published peer-reviewed research to outline the current landscape of the role of SES in the development of speech and language skills among children with hearing loss (HL) who are enrolled in auditory-driven habilitation programs. This essay argues that low SES families may provide sufficient input for their children. The outcome of auditory-driven programs implemented by speech-language pathologists (SLPs) seems to be detached from SES. The role of SES on this developmental trajectory remains unclear, and clinical practice may be related to other validated and robust parameters related to hearing loss.
Keywords: aural rehabilitation; hearing loss; language development; language input; spoken language